PENGARUH METODE PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR MATEMATIKA (Studi Eksperimen pada Siswa Kelas XI SMK Bina Insan Kamil Bekasi) - Julaeha, Siti (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2016)
Abstract: The purpose of this study was to determine differences in the use of methods of cooperative towards mathematics learning outcomes. The research method used was experimental, with a sample of each group of 20 people, who were taken using purposive random sampling technique. The instrument used is a multiple choice test instrument as many as 20 questions. Test requirements on the data analysis is using test Liliefors normality test and homogeneity test using the F test (Fisher), and the results were normal distribution of data as well as meet the test of homogeneity of the data that is homogeneous, so it can proceed with a comparative analysis of non-parametric statistics. Hypothesis test results showed that the value tacount = 6.83506 and ttabel value for ? = 0.05 and df = 38 by 2.02; which means there are significant cooperative learning methods on learning outcomes in mathematics. For further recommended that teachers strive to prepare cooperative learning methods, so that the process of learning mathematics can be both effective and efficient.Keywords: methods, learning outcomes, mathematics